2015
DOI: 10.1016/j.cja.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of flow separation behavior in an over-expanded annular conical aerospike nozzle

Abstract: A three-part numerical investigation has been conducted in order to identify the flow separation behavior--the progression of the shock structure, the flow separation pattern with an increase in the nozzle pressure ratio (NPR), the prediction of the separation data on the nozzle wall, and the influence of the gas density effect on the flow separation behavior are included. The computational results reveal that the annular conical aerospike nozzle is dominated by shock/shock and shock/boundary layer interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In addition, flow separation may develop at the inner wall of the nozzle if the adverse pressure gradient is steep enough across the shock. The separation of the boundary layer inside the supersonic nozzle will generate a separation shock (He et al , 2015). Therefore, large wall divergence or burrs if present inside a supersonic nozzle will generate a complex flow field and its understanding and analysis is quite challenging (Mendonca and Sharif, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, flow separation may develop at the inner wall of the nozzle if the adverse pressure gradient is steep enough across the shock. The separation of the boundary layer inside the supersonic nozzle will generate a separation shock (He et al , 2015). Therefore, large wall divergence or burrs if present inside a supersonic nozzle will generate a complex flow field and its understanding and analysis is quite challenging (Mendonca and Sharif, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The two-equation SST model of Menter [19] was used here to describe the turbulence. Computational results have been compared against the experimental data [20], it was shown that the SST model provides a reasonable prediction of flow separation just downstream of the shock caused by shock-boundary layer interaction inside the nozzle and, therefore, the best capture of the shock location and pressure distribution. In present study, all computations are made using the axisymmetric assumption with a primary motive of a fast and efficient means of obtaining insight into the relevant shock structure and flow separation behavior at various operating conditions.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…Watanabe et al [17] found significant side loads in LE-7A experiments, as well as the vulnerability of some experimental components to damage during nozzle startup and shutdown. Since then, an increasing number of papers have been published studying the transition of separation patterns and its effect on nozzle performance [20][21][22]. Martelli et al [21] numerically investigated a subscale parabolic overexpanded rocket nozzle and attempted to explain the hysteresis cycle between the separation patterns by analyzing the numerical solutions.…”
Section: Introductionmentioning
confidence: 99%